Corporate social responsibility and governance : stakeholders, management and organizational performance in the European Union - Dimitropoulos, Panagiotis; Chatzigianni, Efthalia (New York: Routledge, 2022)
"Corporate social responsibility (CSR) has been developed into a crucial corporate and organizational issue around the world. It has been incorporated within various sectors, countries and includes many types of activities and dimensions. It is common ground that organizations are more inclined today to broader their performance focus form short-term oriented goals towards a long-term social, environmental and value-added perspectives. Under the framework of corporate governance, organizations and companies are motivated to promote fairness, transparency, ethics and accountability in their transactions, while concurrently maintaining enhanced standards of governance. This means that organizations and corporations must align their activities with community aspirations which is an issue falling within the sphere of CSR. Increased attention has been exerted on the organizations regarding their approach towards the needs of various stakeholders. However, a crucial issue that this book attempts to address is the association, intersection and the inter-relationship between governance and CSR within the EU region, not adequately established in the existing literature. The book will show that governance and CSR are highly connected. With the purpose to study the association of CSR with legal, managerial and empirical aspects of governance in corporations and not-for-profit organizations, through various sectors of the economy, the book also intends to provide useful policy implications as well as to offer constructive directions for future research. It will be of value to researchers, academics, practitioners, policymakers, and students in the fields of corporate social responsibility and governance, organizational theory, marketing management, business ethics and human resource management"--
Includes bibliographical references and index.
Keywords: Social responsibility of business